Tibetan book of living and dying - "Rinpoche, Sogyal" (London, 2002)
Written by the Buddhist meditation master and popular international speaker Soygal Rinpoche, this highly acclaimed book clarifies the majestic vision of life and death that underlies the Tibetan Buddhist tradition. It includes not only a lucid, inspiring and complete introduction to the practice of meditation but also advice on how to care for the dying with love and compassion, and how to bring them help of a spiritual kind. But there is much more besides in this classic work, which was written to inspire all who read it to begin the journey to enlightenment and so become 'servants of peace.'
Keywords: Sriritual life